AFLPmatrix_Betula_nana_only_528_115 - Eidesen, Pernille Bronken; Alsos, Inger Greve; Brochmann, Christian (Dryad Digital Repository, 2015)
Subset of the original AFLP matrix (3primers)nwithout populations of B. glandulosa, 115 polymorphic markers and 528 ind